Inventive creativity in architecture: the «forward» and «backward» pathway to creating patentable solutions - Korotich Andrey V.; Fomin Nikita I.; Mironova Ludmila I. (Архитектон, 2023)
The paper presents the authors’ approach to the methodology of sectoral inventive activity, supported by specific examples of how inventive challenges may be solved for various typological groups of architectural and construction objects. The concepts of "forward" and "backward" pathways to creating spot-on inventive solutions in architecture and construction are formulated. The methodological contents and features of these concepts are defined with regard to their practical implementation for obtaining patentable solutions. It is concluded that these techniques need to be taught to architecture and civil engineering students to increase the competitiveness of graduates in the profession and intensify innovation activities in these industries.